Sustainable Housing with Low-Consumption Systems for Island Regions - Serrano Guzmán, Maria Fernanda; Carmona, Jorge Iván; Pérez Ruiz, Diego Darío (Ingeniería Solidaria, 2023)
Introduction: This article highlights the relevant results of the study "Comparative evaluation of technical-economic solutions for internal systems of traditional and sustainable low-energy consumption housing: case study" developed in Pontificia Universidad Javeriana Cali between 2019 and 2021.Problem: The development corresponds to an applicable prototype, specifically in the community of Buenaventura, in Valle del Cauca (Colombia). This community has the highest multidimensional poverty index represented in the population of strata 1, 2, and 3, that often settle in areas with no urban facilities and where construction is made with no design criteria. As a result, the buildings will not satisfy basic needs, including water supply, the disposal of wastewater, and adequate electrical flow.Objective: The objective of this study is to show the technical feasibility and economic viability of sustainable social housing, where the end-user benefits from savings in public services such as energy, water supply, and wastewater.Methodology: The architectural design of the MINGA house, winner of the Solar Decathlon 2019 competition, is used as a platform to include a redesigned residential water supply system, wastewater system and electrical system. The designs of the domestic water supply system, wastewater system and electrical system for the house were developed on top of the original architectural blueprints, allowing for sustainable conditions applicable in low-income housing in the community of Bajamar, Buenaventura.Results: Alternative elements and equipment are proposed for the implementation of low consumption network systems.Originality: Feasibility of implementing low consumption system for homes in island regions.Limitations: System design for one level housing.
Keywords: sustainable; construction; cost; housing